Titanium dioxide (TiO2) as buffer layer in organic solar cell device - Zulkefly, Muhamad Yusuf (2014)
Organic solar cell device has become one of the most promising ways to tackle today's energy issue by offering low production cost, light weight, mechanically flexible and possibility of large area fabrication. Poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl C61-butyric acid methyl ester (PCBM) blends is the most efficient fullerene derivative based donor-acceptor copolymer so far. Current conventional organic solar cell (OSC) device consist of active layers (donor and acceptor) sandwiched by indium tin oxide (ITO) (a high work function, transparent metal oxide) as the anode and low work function metal such as aluminum (Al) as cathode. The recent power conversion energy (PCE) has reached as high as 7.4%. But in spite of high PCE, this device suffers from degradation due to sensitivity of low work function metal to oxygen and moisture in air. An inverted structure of organic solar cell (OSC) device with active layers (donor and acceptor) sandwiched by indium tin oxide (ITO) as the cathode and much higher work function metal and more air stable such as aurum (Au) or silver (Ag) as back contact is an alternative solution to improve the durability. However, ITO is not suitable for electron collection due to large energy band gap between acceptor PCBM and ITO. By introducing thin buffer layer of titanium dioxide (TiO2) between ITO and PCBM may improve overall efficiency of the inverted structure OSC because the new suggested interlayer provide efficient pathway for electrons collections. The aim of this research is to fabricate an inverted organic solar cell (OSC) device consist of ITO/P3HT:PCBM/TiO2/Aurum using sol gel method at room temperature. Investigating the effect of introducing different thickness of the interlayer to the inverted structure OSC is the main objective of this study. An improvement on overall efficiency to the more stable inverted structure OSC is expected at the end of this research.